IMPLEMENTASI NILAI-NILAI PENDIDIKAN ISLAM TERHADAP ADAT MOGAMA’ PADA MASYARAKAT NUANGAN 1 KABUPATEN BOLAANG MONGONDOW - Hamlan Andi Baso Malla; Sjakir Lobud; Muhammad Agung Kadengkang (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2020)
This study deals with "Implementation of Islamic education values ​​to the MoGama tradition 'in the community of Nuangan 1 Village, Bolaang Mongondow Regency". The main discussion in this study is the view of Islam in the 13 implementation of the Gama 'tradition in the village of Nuangan 1 Bolaang Mongondow Regency, and the educational values ​​contained in the stages/implementation of the Gama' custom in the village of Nuangan 1. The purpose of this study is to find out the Islamic view in the 13 stages of the implementation of Gama' and the values ​​of education in the implementation of Gama' in the village of Nuangan 1. This research is qualitative descriptive and viewed with a qualitative approach. Data collection methods include: observation, interviews, documentation, while the data collection is obtained from village heads, traditional leaders, religious leaders and community leaders by presenting data, reducing data, and verifying data. The results of this study are (1) the Islamic view of adat gama' containing the values ​​of Islamic teachings, namely (a) glorifying women. (b) Gathering (c) please help. (d) courtesy of guest. (e) wish for blessing with prayer together. (2) Values ​​of Education in 13 stages Indigenous gamma' (a) treat women well. (b) respect women. (c) treat women well. (d) strengthen family relationships. (e) love women with love. (f) thanks to the female companion who carries an umbrella, (g) being gentle to women. (h) be nice to guests. (i) introduce the bride to the groom's family. (j) thanks to pandamping for accompanying the bride. (k) treat guests well. (l) light hands always give. (m) pray for a newlywed.